Does Pandemic Declined or Maintained Democracy? Two Sides Effects of Pandemic on Democracy in Indonesia - Sholihin, Eko Bagus; Harahap, Raegen; Zalpa, Yulion (UIN Sunan Ampel Surabaya, 2022)
This paper investigates two sides effects of COVID-19 pandemic on democracy in Indonesia. Majority articles on democracy and pandemic argue that COVID-19 pandemic has declined democracy in many countries, including Indonesia. This article, on the one hand agrees with the dominant argument, but on the other hand argues that the COVID-19 pandemic also contributed to maintain democracy. This paper bases democracy on Beetham's notion whose defined democracy as popular control over public affairs with the principles of equality and participation. In order to examine relationship between democracy and pandemic, we use three issues as case studies: the Minerba Bill, the Omnibus Law and data transparency issues. This paper uses qualitative methods and data obtained by literature study regarding civil society’s participation and control in public affairs during the last a year. Two main findings of this paper show that the pandemic has accelerated democratic decline trough two directions, they are from above and from below. Decline from above due to restrictions of freedom of speech and civil participation in public affairs. At the same time, decline from below occurred due to people cleavage in public health issues. In addition, disinformation spread by buzzer which redistributed by other people has been made this situation worse. Otherwise, pandemic also maintained democracy through strengthening civil society's networks and participation marked by strengthening digital activism network toward country’s policy and data transparency. It may be concluded that civil society play a crucial role in maintaining global democracy, especially during the pandemic.